How and when artificial intelligence adoption promotes employee knowledge sharing? The role of paradoxical leadership and technophilia - Xiaoyue Hu; Hongyan Gao; Tesfaye Agafari; Minnie Qing Zhang; Rong Cong (Frontiers in Psychology)
IntroductionThe integration of artificial intelligence (AI) into workplaces has transformed organizational operations, yet its impact on employee knowledge sharing remains underexplored. While AI adoption enhances learning and collaboration, the extent to which employees engage in knowledge sharing depends on leadership styles and attitudes toward technology. This study investigates how AI adoption promotes knowledge sharing through employee learning opportunities, while considering the moderating roles of paradoxical leadership and technophilia.MethodsA survey was conducted with 364 employees across various organizations to examine the proposed relationships. Structural equation modeling (SEM) was employed to test the mediation effect of learning opportunities and the moderating effects of paradoxical leadership and technophilia.ResultsThe findings reveal that AI adoption positively influences employee knowledge sharing, with learning opportunities serving as a key mediating factor. Furthermore, paradoxical leadership and technophilia amplify this relationship, indicating that employees with a strong affinity for technology and those working under paradoxical leaders are more likely to leverage AI for knowledge sharing.DiscussionThese results provide important implications for organizations seeking to maximize the benefits of AI adoption. Managers should foster a paradoxical leadership style and support employees in developing a positive attitude toward technology to enhance knowledge-sharing behaviors. Future research should explore additional contextual factors influencing AI-driven knowledge sharing.